Long-term patient-related quality of life after fracture-related infections of the long bones. Issue 5 (3rd May 2021) - Walter, Nike; Rupp, Markus; Hierl, Katja; Pfeifer, Christian; Kerschbaum, Maximilian; Hinterberger, Thilo; Alt, Volker
Abstract : Aims: We aimed to evaluate the long-term impact of fracture-related infection (FRI) on patients' physical health and psychological wellbeing. For this purpose, quality of life after successful surgical treatment of FRIs of long bones was assessed. Methods: A total of 37 patients treated between November 2009 and March 2019, with achieved eradication of infection and stable bone consolidation after long bone FRI, were included. Quality of life was evaluated with the EuroQol five-dimension questionnaire (EQ-5D) and German Short-Form 36 (SF-36) outcome instruments as well as with an International Classification of Diseases of the World Health Organization (ICD)-10 based symptom rating (ISR) and compared to normative data. Results: With a mean follow-up of 4.19 years (SD 2.7) after the last surgery, the mean SF-36 score was 40.1 (SD 14.6) regarding the physical health component and 48.7 (SD 5.1) regarding the mental health component, compared to German normative values of 48.4 (SD 9.2) (p < 0.001) and 50.9 (SD 8.8) (p = 0.143). The mean EQ-5D index reached 0.76 (SD 0.27) with a mean EQ-5D visual analogue scale (VAS) rating of 65.7 (SD 22.7) compared to reference scores of 0.88 (p < 0.001) and 72.9 (p < 0.001). Mean scores of the ISR did not reveal significant psychological symptom burden, while an individual analysis showed moderate to severe impairments in 21.6% (n = 8) of the patients. Conclusion: Even a mean 4.2 years (SD 2.7) after surgically successful treatment of FRI of long bones, patients report significantly lower quality of life in comparison to normative data. Future clinical studies on FRIs should focus on patient-related outcome measures enabling best possible shared treatment decision-making. Prevention methods and interdisciplinary approaches should be implemented to improve the overall quality of life of FRI patients. Cite this article: Bone Joint Res  2021;10(5):321–327.